RELATION BETWEEN BASIC PHYSICAL CAPABILITIES AND THE THEORETIC KNOWLEDGE LAWS OF THE GAME WITH THE SUCCESS OF REFREEING OF FOOTBALL REFEREES - Rusmir Mrković; Munir Talović; Midhat Mekić; Eldin Jelešković; Haris Alić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The aim of this research is to establish a relation in-between the basic physical capabilities and the theoretic knowledge laws of the game with the success in refereeing of football referees of the Sarajevo Canton. The population from which samples were taken are football referees of the Sarajevo Canton, 90 of them, age span from 18- 45 years of age and who have met the criteria for getting a license to be referees in football matches in the next season at all levels of competition in Bosnia and Herzegovina. The sample of variables in this research covers areas of basic motorics (18), theoretic knowledge laws of the games (17) and the estimate of success in refereeing in football games (7) variables. The results of the final analysis show that the whole system of variables which in this research represent basic physical capabilities and the knowledge Laws of the game by the football referees of the Sarajevo Canton has a statistical connection with the system of variables which in this research makes the success of refereeing of football referees. Since football is an activity that has almost the most complexity (referees are a part of football), we can say that the selected system of variables has a relatively good connection for success and that these variables are very important in order for one referee to perform his task as good as possible at one match.. Of course during the training process attention should be given on the development of all basic physical capabilities, and not only one dimension of the physical area because in general we have to be physically and cognitively be present in order to finish the game at a high rhythm but making mistakes the least as possible